SELF-CONFIDENCE FACTORS OF EFL STUDENTS IN SPEAKING CLASS: A CASE STUDY IN HIGHER EDUCATION - Ami Asnaini; Citra Prasiska Puspita Tohamba; Tri Indah Rusli (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Students’s confidence in speaking English is a crucial factor in the language learning process, particularly for English as a foreign language (EFL) students. However, many students struggle to develo their confidence when contributing to their lack of confidence in speaking English. Using a qualitative approach with Miles and Huberman’s analytical method, data were collected through guideline-based interviews with four EFL students selected using purposive sampling. The findings indicated that low self-confidence among students is influenced by several factors, including mastery experience, vicarious experience, social persuasion, and psychological and emotional states. These four factors are interconnected and collectively shape students’ perceptions of their speaking abilities. The findings highlight the need for greater attention to psychological aspects and the learning environment to support the development of students’ confidence in speaking English.